HYDROLOGIC STUDIES OF THE GLENN CREEK DRAINAGE BASIN NEAR FAIRBANKS, ALASKA. - Dingman,S. Lawrence (1966)
The following observations and tentative conclusions are based on the first summer's study of Glenn Creek and its drainage basin: (1) relationships comprising at-a-station hydraulic geometry are similar to those for larger streams in other areas; (2) the lag time between rainfall and peak storm discharge is much longer for Glenn Creek than for similar-sized streams in mid-latitude regions; (3) hydrograph recessions are drawn out in time relative to those for similar-sized streams in mid-latitude regions; (4) base flow was low in early and mid-summer, rose to a peak in late summer, and very gradually diminished thereafter, accounting for most of the flow in September and October; (5) direct runoff must occur largely as interflow; (6) about 24% of the rain which fell appeared as runoff; (7) the fraction of rainfall appearing as direct runoff varied from 3% to 30%, and showed no seasonal trends; () the suspended and dissolved sediment concentrations of Glenn Creek are within the ranges reported for larger streams in the area; (9) suspended sediment yield was roughly five times as large as dissolved sediment yield for June-October. A number of years of study will be required to confirm these preliminary conclusions and to determine the representativeness of the observations. (Author)